Airborne particle emission rates and doses received in operating rooms from surgical smoke. (15th March 2019) - Buonanno, G.; Capuano, R.; Cortellessa, G.; Stabile, L.
Abstract: The surgical smoke is commonly generated by electrosurgery, i.e. by the heat-producing device used in operating rooms for cutting tissues and coagulating small blood vessels through the use of high-frequency electrical current. Health effects due to the exposure to surgical smoke were recently recognized, thus the scientific community is currently paying more attention to such research field. In particular, studies focusing on the improvement of the effectiveness of filtration systems and mechanical ventilation systems were carried out, nonetheless, a gap of knowledge on the particle concentration levels in the operating rooms and on the emission rate of the surgical procedures still exists. In the present paper an experimental analysis was performed (i) to estimate the particle emission per unit time for several types of surgery for different aerosol metrics and (ii) to measure the dose of both sub-micron and super-micron particles received by workers and patients. To this purpose, samplings were performed in seven operating rooms located in three different Italian hospitals. The median emission rates in terms of particle number and mass concentrations amongst the surgery procedures investigated varied in the 1.59–3.21 × 10 11 part. min −1 and 0.09–0.32 mg min −1 ranges, respectively, leading to corresponding median particle concentration levels of 0.7–1.2 × 10 4 part. cm −3 and 5–13 μg m −3 . Finally, the median particle surface area dose received by personnel working in the operating rooms during the surgery procedures varied from 5 to 12 mm 2 . Highlights: Estimate of particle emission rates for different types of surgery procedures. Measurements of the exposure to sub- and super-micron particles in operating rooms. Estimate of the particle dose received in operating rooms during surgeries. Median particle number emission rates in the 1.59–3.21 × 10 11 part. min −1 range. Median particle mass emission rates in the 0.09–0.32 mg min −1 range.